How Tropical Design as Climate Responsive Design Could Shape Sustainable Living in Germany - Gerwinat, Hanna (Institute for Research and Community Services Udayana University, 2025)
The catastrophic flood disaster of July 2021 in Germany, often named the “century flood,” has underscored the growing urgency of climate change and its impact on urban and rural environments. This event, which claimed over 180 lives and caused widespread damage, is emblematic of a broader trend of increasing extreme weather phenomena such as floods, heatwaves and droughts exacerbated by climate change. As a response there is an emerging need for innovative approaches in architecture, particularly in integrating climate-responsive designs that enhance sustainability and resilience. This paper explores the potential for incorporating tropical architectural principles into German design practices, aiming to address the challenges posed by climate change. By comparing the climate-adaptive strategies of tropical architecture with traditional German building styles this research investigates the feasibility of blending these approaches to create energy efficient, sustainable and culturally sensitive architectural solutions. Through a combination of theoretical analysis and case studies the paper evaluates the opportunities and limitations of such integration, particularly concerning materials, energy efficiency and cultural differences. The study ultimately proposes that a fusion of tropical and German architectural elements could contribute significantly to sustainable living in the face of climate change, offering new pathways for adaptive and environmentally conscious design in Germany.